Corazón que ríe, corazón que llora by Maryse Condé:Who would we be if God were a woman? - García Zamora, Ericka (2023)
The purpose of the article is to analyze the literary work “Corazón que ríe, corazón que llora” by Maryse Condé in attentionto the representation of girls’ childhood and its process of identity construction, in a particular context linked to blackness;and the interpretation of the violent character of education, understood as a colonizing control mechanism.